Nasal carriage of Staphylococcus aureus among healthy veterinary students in Greece, 2017-2018: A cross-sectional cohort study - PAPADOPOULOS, T.; KOMODROMOS, D.; PAPADOPOULOS, P.; MALISSIOVA, E.; TOROUNIDOU, P.; CHOULIARA, E.; ZDRAGAS, A.; CHALIGIANNIS, I.; PARDALI, D.; SERGELIDIS, D. (Journal of the Hellenic Veterinary Medical Society, 2021)
The epidemiology of Staphylococcus spp., Staphylococcus aureus and MRSA among veterinary students in Greece during 2017-2018 is reported. Nasal swabs and a standardized questionnaire from 160 healthy veterinary students were used to identify potential risk factors for colonization. Antimicrobial susceptibility testing, pvl, mecA, mecC, staphylococcal enterotoxin genes and PFGE were used to characterize S. aureus isolates. Overall, 76% and 19% of the students were colonized by Staphylococcus spp. and S. aureus but none by MRSA. Students with a prior visit to a hospital were 1.33 and 2.25 times more likely to be colonized by Staphylococcus spp. and S. aureus, respectively while, 94% of the S. aureus isolates were resistant to penicillin, 68% to amoxicillin/clavulanic acid and 12% were multidrug-resistant. Staphylococcal enterotoxin genes were detected in 32% of the S. aureus isolates, while PFGE showed heterogeneity. Although MRSA was not detected, the high rate of Staphylococcus spp. Colonization suggests the need of sustained implementation of strict hygiene practices among students and the staff involved in veterinary training. The results of the present study add useful information for the assessment of the risks associated with staphylococcal infection in veterinary students.